2020
DOI: 10.1161/hypertensionaha.120.15384
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cardiovascular Defense to Hypotensive Stress in the Chronically Hypoxic Fetus

Abstract: The hypoxic fetus is at greater risk of cardiovascular demise during a challenge, but the reasons behind this are unknown. Clinically, progress has been hampered by the inability to study the human fetus non-invasively for long period of gestation. Using experimental animals, there has also been an inability to induce gestational hypoxia while recording fetal cardiovascular function as the hypoxic pregnancy is occurring. We use novel technology in sheep pregnancy that combines induction of controlled chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…However, the endocrine data show that this model of early‐onset hypoxic pregnancy was not associated with elevations in glucocorticoids either in the maternal of fetal circulation. This outcome is in keeping with studies of ovine pregnancy at high altitude, 58 and with studies of ovine pregnancy exposed to isobaric chronic hypoxia at sea level 36,59 . It has been proposed that hypoxic pregnancy downregulates adrenocortical sensitivity in fetal life, as an adaptive response to protect against preterm birth induced by chronic hypoxic stress 58 .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, the endocrine data show that this model of early‐onset hypoxic pregnancy was not associated with elevations in glucocorticoids either in the maternal of fetal circulation. This outcome is in keeping with studies of ovine pregnancy at high altitude, 58 and with studies of ovine pregnancy exposed to isobaric chronic hypoxia at sea level 36,59 . It has been proposed that hypoxic pregnancy downregulates adrenocortical sensitivity in fetal life, as an adaptive response to protect against preterm birth induced by chronic hypoxic stress 58 .…”
Section: Discussionsupporting
confidence: 69%
“…This level of hypoxia simulates ~ 3600 m above sea level, the altitude at which pregnancy complications have been demonstrated to be significantly increased in human populations 6‐8,33‐35 . In experiments in sheep, in which the fetus can be catheterized long term, we have also shown that this level of reduced maternal oxygenation during pregnancy yields fetal arterial PO 2 values between 12 and 14 mmHg 7,36,37 . This is the PO 2 measured by cordocentesis in human fetuses in pregnancy affected by chronic fetal hypoxia 38 .…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…, 23 Plotting the mean arterial pressure responses to infusion of pressor and depressor drugs against heart rate responses can be used to determine cardiac baroreflex function and investigate autonomic mechanisms in the control of in vivo cardiovascular function 13 20 22 , 24 , 25 FVR responses to SNP plotted against the fall in arterial blood pressure further permits determination of vasomotor baroreflex function in vivo 26 . Sustained infusion of SNP over 30 min can also be used to study the cardiovascular response to an acute hypotensive challenge 27 .…”
Section: Discussionmentioning
confidence: 99%